2016
DOI: 10.1038/mt.2015.220
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo CRISPR/Cas9 Gene Editing Corrects Retinal Dystrophy in the S334ter-3 Rat Model of Autosomal Dominant Retinitis Pigmentosa

Abstract: Reliable genome editing via Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR)/Cas9 may provide a means to correct inherited diseases in patients. As proof of principle, we show that CRISPR/Cas9 can be used in vivo to selectively ablate the rhodopsin gene carrying the dominant S334ter mutation (RhoS334) in rats that model severe autosomal dominant retinitis pigmentosa. A single subretinal injection of guide RNA/Cas9 plasmid in combination with electroporation generated allele-specific disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
195
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(199 citation statements)
references
References 25 publications
2
195
0
2
Order By: Relevance
“…Recently, SpCas9 has been proven to be a powerful tool for making precise genomic perturbations in vivo. It has been used in vivo to study the function of genes in the liver and brain [42,43] and to cure metabolic and genetic diseases in animal models [44]. Here, we demonstrated that SpCas9 can be used to disrupt the genes in adult mouse islets.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, SpCas9 has been proven to be a powerful tool for making precise genomic perturbations in vivo. It has been used in vivo to study the function of genes in the liver and brain [42,43] and to cure metabolic and genetic diseases in animal models [44]. Here, we demonstrated that SpCas9 can be used to disrupt the genes in adult mouse islets.…”
Section: Discussionmentioning
confidence: 78%
“…Partial phenotypic recovery has been observed in these studies Nelson et al 2016;Tabebordbar et al 2016). The use of CRISPR in vivo to ablate the rhodopsin gene carrying the dominant S334ter mutation in rats with severe autosomal dominant retinitis pigmentosa also highlights the use of genetic correction in disease (Bakondi et al 2016). These proof-of-principle experiments may be the first steps towards overcoming many currently incurable genetic diseases.…”
Section: Gene Editing In Vivo To Treat Genetic Diseasesmentioning
confidence: 80%
“…This has not been tried in human patients yet; however, in trials with rats, disruption of the dominant-negative allele of rhodopsin (S334Ter) by inducing such “knockout” mutations specifically in the mutant allele have restored normal function to photoreceptors. 29 The NHEJ repair function after cutting results in the disruption of the mutant allele, such that the misfolded rhodopsin protein does not accumulate in photoreceptors and lead to death of the cells.…”
Section: A New Gene Editing Toolmentioning
confidence: 99%